Kenaf Core Particleboard and Its Sound Absorbing Properties - Saad, Mohamad Jani; Kamal, Izran (Journal of Science and Technology, 2012)
In this study, kenaf (Hibiscus cannabinus) core particleboards as insulation boards were manufactured. The boards were fabricated with three different densities i.e. 350 kg/m3, 450 kg/m3 and 550 kg/m3 at urea formaldehyde resin (UF) loadings of 8%, 10% and 12% (w/w) based on the dry weight of the kenaf core particles. The fabricated boards were evaluated for its noise acoustical coefficients (NAC) by following the ASTM E1050-98 standard requirements. The study revealed that boards with higher kenaf fiber loading and UF loading gave less NAC.